2021
DOI: 10.1097/meg.0000000000002044
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and sarcopenia are prevalent among inflammatory bowel disease patients with clinical remission

Abstract: Aim The aim of this study was to evaluate nutritional status and sarcopenia in patients with inflammatory bowel disease (IBD) in clinical remission. Methods A total of 344 patients with IBD in clinical remission were included in this cross-sectional study. Patients with clinical activity (Harvey-Bradshaw index >5 for Crohn’s disease and partial Mayo scores ≥5 for ulcerative colitis) were excluded. Sociodemographic, clinical, and anthropometric data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Table 1 shows the evaluation methods and frequency of sarcopenia reported in recent years in patients with IBD [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In more than half of the reports, computed tomography (CT, L3 level) is used to assess sarcopenia, but many reports only use muscle mass assessment to determine sarcopenia, while a few include grip strength and walking speed in the assessment of sarcopenia [ 17 ]. Furthermore, unlike primary sarcopenia [ 4 , 5 ], no reference values have been established for muscle mass, grip strength, or walking speed in patients with IBD.…”
Section: Methods and Frequency Of Sarcopenia Assessment In Patients With Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the evaluation methods and frequency of sarcopenia reported in recent years in patients with IBD [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In more than half of the reports, computed tomography (CT, L3 level) is used to assess sarcopenia, but many reports only use muscle mass assessment to determine sarcopenia, while a few include grip strength and walking speed in the assessment of sarcopenia [ 17 ]. Furthermore, unlike primary sarcopenia [ 4 , 5 ], no reference values have been established for muscle mass, grip strength, or walking speed in patients with IBD.…”
Section: Methods and Frequency Of Sarcopenia Assessment In Patients With Ibdmentioning
confidence: 99%
“…Table 1 shows the evaluation methods and frequency of sarcopenia reported in recent years in patients with IBD [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In more than half of the reports, computed tomography (CT, L3 level) is used to assess sarcopenia, but many reports only use muscle mass assessment to determine sarcopenia, while a few include grip strength and walking speed in the assessment of sarcopenia [17].…”
Section: Methods and Frequency Of Sarcopenia Assessment In Patients With Ibdmentioning
confidence: 99%
“…The association of malnutrition and sarcopenia in IBD patients is controversial. Indeed, it is noteworthy that while malnutrition in IBD is characterized by weight loss during the acute phase of disease followed by a gradual recovery during disease remission, sarcopenia may be present even in IBD patients in remission and not only with low but also normal or elevated values of BMI (85)(86)(87).…”
Section: Malnutritionmentioning
confidence: 99%
“…Notably, sarcopenic IBD patients had lower preoperative serum levels of albumin and higher preoperative serum levels of C-reactive protein, deemed markers of malnutrition/inflammation and predictive factor of surgical negative outcome ( 86 ). Furthermore, a recent cross-sectional study involving 344 IBD patients in clinical remission revealed an increased risk of sarcopenia in malnourished patients ( 87 ).…”
Section: Studies Exploring Ibd and Sarcopeniamentioning
confidence: 99%
“…In IBD patients, malnutrition and excess weight can coexist with sarcopenia, which is a skeletal muscle syndrome characterized by progressive and generalized reduction in the quantity and quality ( i.e. strength or physical performance) of muscle mass[ 76 ]. The etiology of sarcopenia is multifactorial, involving aging, physical inactivity, presence of other diseases ( e.g.…”
Section: Nutritional Status and Postoperative Complicationsmentioning
confidence: 99%